Sub-nanosecond pulse generation with reduced ringing - Shahid, Zeeshan (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
This dissertation presents the design, working principle, simulation results and analysis of a sub-nanosecond pulse generator. This design is a mix of devices and ideas derived from contemporary reported works with results showing up ringing both at the leading and trailing ends of the pulse. Additionally, experimental implementation requires fabrication on chip designs, making the final product to be an expensive and time consuming venture. The design is simulated using NI MULTISIM tool, and the achieved results are supported by the relevant theory of the components involved. The functionality of the circuit shows how pulses are generated as final product when proceeding from input onward to the output. The resulting pulse is studied for its normal pulse characteristic parameters including rise and fall time, pulse width, amplitude and with a power spectral density. The achieved characteristic parameters show a clear margin of the utility of the suggested circuit when compared with results of contemporary works. The waveform results show that pulses generated are of high quality with a good level of amplitude stability over a wide radio frequency range. Such features are leverage and key elements for high performance impulse radar sensing. The signal power results prove the signal to be of low power, creating a possibility of low power simple transmitter designs well within the FCC defined range. The limitation of this work lies in the laboratory implementation demanding for high response measurement and monitoring equipments for an effective display of the characteristics of pulses in terahertz range.